Sub-fossil Chironomidae (Diptera) from lake sediments in Central America: a preliminary inventory - Hamerlik, Ladislav; Da Silva, Fabio Laurindo; Wojewódka, Marta (Zootaxa, 2018)
The chironomid diversity of Central America is virtually underestimated and there is almost no knowledge on the chironomid remains accumulated in surface sediments of lakes. Thus, in the present study we provide information on the larval sub-fossil chironomid fauna from surface sediments in Central American lakes for the first time. Samples from 27 lakes analysed from Guatemala, El Salvador and Honduras yielded a total of 1,109 remains of four subfamilies. Fifty genera have been identified, containing at least 85 morphospecies. With 45 taxa, Chironominae were the most specious and also most abundant subfamily. Tanypodinae with 14 taxa dominated in about one third of the sites. Orthocladiinae were presented by 24 taxa, but were recorded in 9 sites, being dominant in only one site. Podonominae were collected only in one locality. Head capsules of Heterotrissocladius found in the high elevation lake Magdalena, Guatemala, represent a first record for the Neotropical region. Both relative abundance and species richness of Chironominae and Orthocladiinae showed significant relationship to elevation, while Tanypodinae were indifferent. Hopefully, the list of taxa provided by our study will be a base line for future limnological and paleolimnological investigations using chironomid remains in the region.